2015
DOI: 10.1089/omi.2015.0116
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants Associated with Type 2 Diabetes in a Black South African Population of Setswana Descent: African Populations Diverge

Abstract: The increasing worldwide prevalence of type 2 diabetes mellitus (T2D) is a serious global health concern. Although T2D has a strong genetic etiology, limited knowledge exists about the common variants associated with it in the black South African population. This study set out to evaluate the association of previously reported common variants in other world populations with T2D susceptibility in a black South African population of Setswana descent. A case-control study design of 178 cases and 178 controls nest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In single studies, the ABCC8 and Haptoglobin SNPs were found to be associated with T2DM among Nigerians [ 51 ] and Ghanaians [ 52 ], respectively. Two polymorphisms in two genes ( PSMD6 and C2D4B ) were found to be nonsignificantly associated with T2DM in Black South Africans after correcting for multiple testing [ 53 ]. Polymorphisms in KCNJ11 (rs5219) was found to be nonsignificantly associated with T2DM among Ghanaian [ 49 ] and Nigerian [ 54 ] populations but significant among Mauritanians [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…In single studies, the ABCC8 and Haptoglobin SNPs were found to be associated with T2DM among Nigerians [ 51 ] and Ghanaians [ 52 ], respectively. Two polymorphisms in two genes ( PSMD6 and C2D4B ) were found to be nonsignificantly associated with T2DM in Black South Africans after correcting for multiple testing [ 53 ]. Polymorphisms in KCNJ11 (rs5219) was found to be nonsignificantly associated with T2DM among Ghanaian [ 49 ] and Nigerian [ 54 ] populations but significant among Mauritanians [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The world-wide prevalence of cases of type 2 diabetes and pre-diabetes have been spiralling out of control, and not only in developed countries, but also in third-world countries [1–4], with more than half a billion cases expected by 2030 [5]. Co-morbidities are also a major health burden on all health systems, and include hypoglycaemia, hypertension, dyslipidaemia, cardiovascular and heart related deaths, stroke, kidney disease, eye problems and also amputations [6].…”
Section: Introductionmentioning
confidence: 99%
“…The databases from where the articles were retrieved are shown in Table 1. The studies relied on datasets from different sources: T1DGC [55], WTCCC [56], UFDI, Iranian Hospitals [35], the PURE study [57], UK hospital [45], GoDARTS [58], MPP [59], BPS [60], Framingham…”
Section: Selected Studies For the Systematic Reviewmentioning
confidence: 99%